Impact of Irrigation Periods and Humic Acids on the Vegetative Growth Parameters of Sunflower Plants - Sahan , Salih Mahdi; Al-Mugher , Haider Abdul-Hussein; Al-Gharawi , Jassim Kassim (American Journal of Botany and Bioengineering, 2025)
A field experiment was conducted during the fall season (2024), at the Agricultural Research Station affiliated with the College of Agriculture, Al-Muthanna University. The aim was to study the effect of humic and fulvic acid levels and irrigation frequency on the growth parameters of sunflowers (Shamous variety). The experiment was conducted using a randomized complete block design (RCBD), according to a split-plot design and with three replicates. The experiment included (36) experimental units representing all combinations of the study factors and their replicates. The main plots represented the number of irrigations. The sub-plots (humic and fulvic) represented the effect of humic acids. Organic fertilizer (a mixture of humic and fulvic) was added in two batches: the first after thinning and the second after the flower disc appeared. The results indicated that 13 irrigations (W3) compared to 11 irrigations (W2) significantly improved plant height, while a concentration of 45 kg ha-1 significantly affected this trait compared to the control treatment. For stem diameter, it was observed that the H0W3 treatment yielded the highest average compared to the H0W1 treatment, while the remaining studied traits were not significantly affected by the study factors.